METHODOLOGY OF THE ASSESSMENT FOR ALGORITHMIC COMPLEXITY OF PARALLEL IMPLEMENTATION OF THREE-DIMENSIONAL POLYADIC CODING - Ryabkhа Yu. M. (Science-based technologies, 2014)
It is shown that further enhancement of video information technologies in the direction of resolution enhancement that inevitably lead to the sharp growth of video data volumes. Origin of a contradiction between requirements on the one hand concerning safety of the led-up information, and on the other side of relatively timeliness of its receiving is in turn justified. One of the effective directions of creation of three-dimensional coding technologies are the code structures created for three-dimensional poliadic numbers. It is developed methodologies of an assessment of complexity of three-dimensional three-level poliadic coding algorithmic implementation with use of the parallel diagram of processing. The methodology is based on property of the three-dimensional poliadic coding consisting in a possibility to parallelize computation of a code for all three-dimensional poliadic number (TDPN). It is justified that the number of operations is reduced as result of the following multisequencing: parallel computation of a code at the expense of sequential on conjugate enlargement of discharges on columns; parallel computation of line code at the expense of sequential on conjugate enlargement of discharges in the lines.